Respuesta :
For this case we have an expression of the form:
x ^ 2 - 5x + _____ = 7
To complete the square, we must add to both sides of the equation a constant of the form:
(b / 2) ^ 2
We have then:
x ^ 2 - 5x + (-5/2) ^ 2 = 7 + (-5/2) ^ 2
Rewriting we have:
x ^ 2 - 5x + 6.25 = 7 + 6.25
x ^ 2 - 5x + 6.25 = 13.25
Answer:
The constant term that should be used to complete the square is:
6.25
x ^ 2 - 5x + _____ = 7
To complete the square, we must add to both sides of the equation a constant of the form:
(b / 2) ^ 2
We have then:
x ^ 2 - 5x + (-5/2) ^ 2 = 7 + (-5/2) ^ 2
Rewriting we have:
x ^ 2 - 5x + 6.25 = 7 + 6.25
x ^ 2 - 5x + 6.25 = 13.25
Answer:
The constant term that should be used to complete the square is:
6.25
the correct answer is 25/4 so choose letter B as you answer have beautiful day.